Dobri muslimani, moderni državljani Islamski preporod med Huiji na severozahodu Kitajske - Veselič, Maja (Prostor, kraj, čas, 2016)
This book ('Good Muslims, Modern Citizens: Hui Islamic Revival in Northwest China') explores the hegemonic models of modernity and their alternatives in contemporary China through an anthropological investigation of Islamic revival among Hui, a Chinese-speaking ethnoreligious minority. Examining a variety of formal and informal, religious and semi-religious education activities aimed at children and youth in the poor areas of Northwest China, where Hui communities are most numerous, it traces the impact of nation-building and state modernization policies as well as the intensification of religious and economic contacts with Muslim majority countries on the (self)perceptions of Hui as an inalienable part of the Chinese nation on the one hand and members of the global ummah on the other. The detailed ethnographic study of religious life on a university campus reveals how young Hui negotiate their desires and forge their identities as simultaneously modern, educated Chinese citizens and pious Muslims. With its intimate portrayal of how global transformations are expressed and experienced in the everyday life of people on the margins of China and Muslim world, this book contributes to the growing literature on contemporary Chinese and Muslim religiosities.